IDENTIFIKASI CEMARAN LOGAM BERAT DALAM EKSTRAK ETANOL 70% BUAH OKRA (Abelmoschus esculentus L.): IDENTIFIKASI CEMARAN LOGAM BERAT DALAM EKSTRAK ETANOL 70% BUAH OKRA (Abelmoschus esculentus L.) - CHANDRA, PRA; Efrilia, Mega; Prayoga, Tria; Lisnawati, Nia (Sam Ratulangi University, 2024)
Okra fruit (Abelmoschus esculentus L.) is a natural ingredient that can be developed as a raw material for natural-based medicines. The phytochemical compounds contained in okra fruit are flavonoids, alkaloids, saponins, tannins, triterpenoids, coumarins, phenolics, glycosides. steroids and alkaloids, α-cellulose, hemicellulose, lignin, components. Okra fruit with varying secondary metabolite content produces positive effects on the potential pharmacological activity of okra fruit. The potential pharmacological activity of okra fruit is as antidiabetic, hypolipidemic, antioxidant, antimicrobial, anticancer, wound healing, hepatoprotective, immunomodulatory, neuroprotective and gastroprotective in addition to cardioprotective activity. Extracts must meet extract quality parameters, one of which is non-specific parameters for heavy metal contamination. This research aims to determine the heavy metal contamination content of Lead (Pb), Cadnium (Cd) and Arsenic (As) contained in the 70% ethanol extract of okra fruit. The okra fruit extraction process was carried out by maceration with 70% ethanol solvent. Determination of heavy metal content using an atomic absorption spectrophotometer instrument. The research results showed that the 70% ethanol extract of okra fruit did not contain Lead (Pb), Cadnium (Cd) and Arsenic (As). Keywords: Okra fruit, Abelmoschus esculentus, Heavy Metal Contamination